Thermo-mechanical volume change behaviour of Opalinus Clay. (December 2016) - Favero, Valentina; Ferrari, Alessio; Laloui, Lyesse
Abstract: The paper examines the thermo-mechanical volume change behaviour of Opalinus Clay in relation to different stress conditions and overconsolidation ratio (OCR) values and evaluates the impact of temperature on some hydro-mechanical properties of this material. To this aim, a focused experimental campaign consisting in high-temperature/high-pressure oedometric tests has been carried out. The results show that the thermo-mechanical volume change behaviour of Opalinus Clay is heavily affected by the OCR: thermal expansion is found when the heating is carried out at high OCR, whereas irreversible thermal compaction is observed when heat is applied at a vertical effective stress that is sufficiently close to the vertical effective yield stress. The study of the thermal cyclic behaviour shows that expansive irreversible strains can occur upon first heating at high OCR and that a reversible behaviour follows during subsequent thermal cycles. The experimental results reveal an impact of temperature on yielding: a decrease in the yield threshold is detected when compression is applied at high temperature with respect to the yield threshold found at low temperature. Compressibility and swelling indexes are not significantly influenced by thermal changes, as well as the oedometric modulus and the secondary compression coefficient, whereas consolidation processes are found to occur faster at high temperature. The obtained results are presented in this paper together with a description of the testing device and experimental procedure employed. Highlights: Insights on the thermal behaviour of Opalinus Clay at different stress and overconsolidation ratio values are presented. The thermal cyclic behaviour of Opalinus Clay is analysed. The irreversible features in the thermo-mechanical volume change behaviour of the shale are highlighted. The effect of temperature on the hydro-mechanical performance of the material is addressed.